Finance and rural development in West Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Finance and rural development in West Africa is the title of the proceedings from the seminar on the subject held in Ouagadougou, Burkina Faso